Implementasi Program Edukasi Cuci Tangan Berbasis Permainan untuk Meningkatkan Perilaku Pencegahan Demam Tifoid pada Anak Sekolah SDN 1 Dono Tulungagung - Nurjanah, Mutia Hariani; Fuzianingsih, Eka Novia; Kumalasari, Nurul Chamidah; Sulastri, Sulastri; Martha, Rahma Diyan; Wijaya, Anas Fadli; Widayanti, Sindi Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
Typhoid fever remains a public health issue in Indonesia, especially among elementary school children who are vulnerable due to poor hygiene habits, particularly not washing hands. Traditional education methods often fail to change children's behavior, so more engaging and interactive approaches are needed. This activity aimed to improve handwashing behavior through educational games. A quasi-experimental method with a pretest-posttest control group design was used. The intervention involved 40 students from SDN 1 Dono, Tulungagung, using games like hygiene-themed snakes and ladders and handwashing step cards. Evaluation was conducted through pretest and posttest assessments and group discussions with teachers. Results showed a significant improvement in the intervention group from 70% (poor category) to 83% (good category), with a p-value of 0.000. In contrast, the control group showed no significant change (p = 0.213). Educational games proved effective in improving students’ handwashing behavior and can be a preventive strategy against typhoid fever in schools.